2020
DOI: 10.31410/limen.2020.25
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Efficiency in Africa: Evidence From Random Walk Hypothesis

Abstract: This paper aims to test the efficient market hypothesis, in its weak form, in the stock markets of BOTSWANA, EGYPT, KENYA, MOROCCO, NIGERIA and SOUTH AFRICA, in the period from September 2, 2019 to September 2, 2020. In order to achieve this analysis, we intend to find out if: the global pandemic (Covid-19) has decreased the efficiency, in its weak form, of African stock markets? The results therefore support the evidence that the random walk hypothesis is not supported by the financial markets analyzed in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 71 publications
4
8
0
Order By: Relevance
“… Hypothesis 1: ESG and conventional indices are efficient We found that Moroccan financial indices are inefficient, with an exponent of 0.62352 for the MASI and 0.61844 for the Casa ESG 10 sustainability index. This finding is consistent with the results of Rejichi and Aloui (2012), Dias andSantos (2020), andSmith et al (2002).…”
Section: Hypotheses Tests and Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“… Hypothesis 1: ESG and conventional indices are efficient We found that Moroccan financial indices are inefficient, with an exponent of 0.62352 for the MASI and 0.61844 for the Casa ESG 10 sustainability index. This finding is consistent with the results of Rejichi and Aloui (2012), Dias andSantos (2020), andSmith et al (2002).…”
Section: Hypotheses Tests and Discussionsupporting
confidence: 93%
“…It is also the case for the Egyptian sustainability index (EGX S & P) (exponent of 0.63747). These results align with the results of Al-Jafari and Abdulkadhim Altaee (2011), Dias andSantos (2020), andSmith et al (2002). Al-Jafari and Abdulkadhim Altaee (2011) studied efficiency in the Egyptian stock market using several approaches including unit root test, run test, and variance ratio tests.…”
Section: Hypotheses Tests and Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In another way, the prices of securities that are traded in an efficient financial market reflect all available information and adjust fully and quickly to new information. In addition to the assumption that the information available in the market is free Dias et al, , 2022Dias and Santos, 2020;Vasco et al, 2021).…”
Section: Introductionmentioning
confidence: 99%